Addendum: Development and evaluation of a school-based physical literacy intervention for children in Germany: protocol of the PLACE study - Pöppel, Katharina; Schmittwilken, Louisa; Carl, Johannes (Frontiers in Sports and Active Living, 2024)
Pilot studies serve to explore the feasibility of assessment instruments and intervention arrangements. As there have not been any validated German physical literacy (PL) assessments for children, we originally included four translated instruments into the pilot phases of the PLACE study, which aimed to test the effectiveness of a theory-based PL intervention for the extracurricular time at primary schools for pupils in Bremen of grades three to four. Unfortunately, the exploratory analyses revealed that all quantitative PL instruments, despite extensive revision throughout the pilot waves, showed insufficient reliability and validity. Against this background, we have to adjust the main phase of the study and deviate meaningfully from our initial study protocol with mixed-methods character [Carl, J., Schmittwilken, L., & Pöppel, K. (2023). Development and evaluation of a school-based physical literacy intervention for children in Germany: protocol of the PLACE study. Frontiers in Sports and Active Living, 5, 1155363. doi: 10.3389/fspor.2023.1155363] by dissolving the quantitative part in favor of a qualitative study with multiple data sources (multiperspective discussion panel, session protocols, group interviews). We want to transparently communicate this re-arrangement prior to the main phase.